2003
DOI: 10.1074/jbc.m306729200
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin Is Not Required to Maintain Mitochondrial DNA Stability or Cell Viability for Saccharomyces cerevisiae Grown at Elevated Temperatures

Abstract: In eukaryotic cells, the phospholipid cardiolipin (CL) is primarily found in the inner mitochondrial membrane. Saccharomyces cerevisiae mutants, unable to synthesize CL because of a null allele of the CRD1 gene (encodes CL synthase), have been reported with different phenotypes. Some mutants, when grown on a nonfermentable carbon source at elevated temperatures, exhibit mitochondrial DNA instability, loss of viability, and significant defects in several functions that rely on the mitochondrial energy transduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 26 publications
6
42
1
Order By: Relevance
“…Yeast Strain and Growth Media-Wild type yeast strain DL1 and its CRD1 null derivatives (crd1⌬) lacking cardiolipin, YZD5 (15), were grown at 30°C in YPEG growth medium consisting of 1% Bacto yeast extract, 2% Bacto peptone, and 1% ethanol (v/v) and 3% glycerol as a carbon source.…”
Section: Methodsmentioning
confidence: 99%
“…Yeast Strain and Growth Media-Wild type yeast strain DL1 and its CRD1 null derivatives (crd1⌬) lacking cardiolipin, YZD5 (15), were grown at 30°C in YPEG growth medium consisting of 1% Bacto yeast extract, 2% Bacto peptone, and 1% ethanol (v/v) and 3% glycerol as a carbon source.…”
Section: Methodsmentioning
confidence: 99%
“…CL synthesis shares the same precursor, CDP-diacylglycerol, with the main cellular phospholipids, yet it differs significantly from other phospholipids in its acyl-chain composition that is characterized by a high degree of unsaturated fatty acids. Although cardiolipin was believed to be essential to support mitochondrial function, mutants defective in cardiolipin synthase (Crd1p) are viable and display only moderate defects of mitochondrial function (6,7). More severe is a defect in the first committed step of CL synthesis, catalyzed by phosphatidylglycerolphosphate synthase Pgs1p/Pel1p (8).…”
Section: Cardiolipin (Cl)mentioning
confidence: 99%
“…More recently, Zhang et al (13) reported that several phenotypes in the CL-deficient mutant were exacerbated by reduced expression of PET56 and concluded that phenotypes associated with the crd1⌬ mutant should be reevaluated. In this report, we examined the role of pet56 in crd1⌬ mutant phenotypes and concluded the following.…”
Section: Uncoupled Oxidative Phosphorylation In Crd1⌬mentioning
confidence: 99%
“…Reduced expression of PET56 was found to slow growth, decrease mitochondrial DNA stability, and decrease cell viability at elevated temperatures (14,15). It was suggested that the growth defects of crd1⌬, which resemble the phenotypes of pet56, were due to reduced PET56 expression rather than lack of CL (13). However, as mitochondrial defects were observed in crd1⌬ as compared with isogenic wild type cells, the presence of a pet56 mutation in both crd1⌬ and wild type could not explain the mitochondrial defects.…”
mentioning
confidence: 99%
See 1 more Smart Citation